2016
DOI: 10.1016/j.ajog.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response to 17-alpha hydroxyprogesterone caproate for prevention of recurrent spontaneous preterm birth

Abstract: Background Prematurity is the leading cause of neonatal morbidity and mortality amongst non-anomalous neonates in the United States. Intramuscular 17-alpha hydroxyprogesterone caproate (17OHP-C) injections reduce the risk of recurrent prematurity by approximately one third. Unfortunately, prophylactic 17OHP-C is not always effective, and one-third of high-risk women will have a recurrent PTB despite 17OHP-C therapy. The reasons for this variability in response are unknown. Previous investigators have examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 21 publications
3
20
0
3
Order By: Relevance
“…10 Our prior study included 155 women; 37 (24%) were classified as non-responders, which is similar to the 21% non-responder rate in the current study. In that study, we also identified the gestational age of the earliest previous spontaneous PTB, significant vaginal bleeding or abruption, first-degree family history of SPTB, and preterm birth of the penultimate pregnancy as risk factors for reduced response to 17OHP-C. 10 We have confirmed these results in the current study. We were unable to evaluate family history in the current report, as this information was not collected as part of the original RCT.…”
Section: Commentsupporting
confidence: 68%
See 3 more Smart Citations
“…10 Our prior study included 155 women; 37 (24%) were classified as non-responders, which is similar to the 21% non-responder rate in the current study. In that study, we also identified the gestational age of the earliest previous spontaneous PTB, significant vaginal bleeding or abruption, first-degree family history of SPTB, and preterm birth of the penultimate pregnancy as risk factors for reduced response to 17OHP-C. 10 We have confirmed these results in the current study. We were unable to evaluate family history in the current report, as this information was not collected as part of the original RCT.…”
Section: Commentsupporting
confidence: 68%
“…8,10 To review, the difference between the earliest delivery gestational age and the delivery gestational age with 17OHP-C was calculated, and termed the ‘17OHP-C effect.’ Women with a 17OHP-C effect of ≥3 weeks (i.e., the individual’s pregnancy or pregnancies treated with 17OHP-C delivered at least 3 weeks later compared to the gestational age of the earliest PTB without 17OHP-C treatment) were considered 17OHP-C responders; this designation was made in part by using data originally published by Bloom, et al which showed that 70% of women with recurrent PTB will experience recurrence within 2 weeks of their initial PTB. 15 Women with a negative overall 17OHP-C effect and those with an overall 17OHP-C effect of <3 weeks were classified as non-responders.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, we and others have demonstrated that maternal genotype, 9 number of prior PTBs, 10,11 prior PTB due to preterm premature rupture of membranes (PPROM), 12,13 and maternal weight/obesity 14,15 are significant modifiers of the effectiveness of fixed-dose 17OHP-C treatment. It is thus important to understand how other recognized PTB risk factors, such as smoking, might impact the effectiveness of 17OHP-C treatment.…”
mentioning
confidence: 99%